Pengaruh Kompetensi dan Pelaksanaan Audit Internal dalam Menunjang Efektifitas Pengendalian Internal Penjualan - Elisia Elisia; Stefanus Ariyanto (Bina Nusantara University, 2010)
PT Inti Dufree Promosindo is a subsidiary of PT Sona Topas Tourism Industry, Tbk. The company is one of the biggest retail companies that sell local and imported products. This business is also called duty free shop. PT. Inti Dufree Promosindo have problems in evaluate the infuence of the effectiveness of its internal audit function towards sales internal control due to large number of sales transactions occurred. The research result shows that the auditor competence and audit process variable have low but significant influence to sales internal control effectiveness (Coefficient determination 22.7%), and so that the audit process variable that have low but significant influence to sales internal control effectiveness (Coefficient determination 36.8%). However, the combination of the two variables tested with linear regression shows that both variables simultaneously have strong influence to sales internal control effectiveness. Based on the result of multiple linier regression analysis the determination coefficient is 47, 4%. This shows that auditor competence and audit process simultaneously have a significant effect in supporting internal sales control effectiveness.